SPIRALS: An Approach to Non-Linear Thinking for Medical Students in the Emergency Department - Small, Rebecca N (Cureus, 2020)
Context We lack guidelines to inform the necessary components of an emergency medicine undergraduate rotation. Traditionally, clinical reasoning has been taught using linear thought processes likely not ideal for diagnostic and management decisions made in the emergency department.  Methods We used the Delphi method to obtain consensus on a set of competencies for undergraduate emergency medicine that illustrate the non-linear concepts we believe are necessary for learners. Competencies were informed by a naturalistic observational study of emergency physicians. A survey outlining these competencies was subsequently circulated to emergency physicians who rated their relative importance. Results Eleven competencies were included in Round 1, all rated within the “for consideration” for inclusion range. This was reduced to 10 competencies in Round 2, which was only marginally more definitive with respondents rating one competency in the “definite inclusion range” and the remaining in the “for consideration” range.  Conclusions This study was conducted to address a gap in the current undergraduate emergency medicine curriculum. Consensus on the relative importance of each competency was not achieved, though we believe that the competencies that arose from this study will help medical students develop the non-linear thinking processes necessary to succeed in emergency medicine.